A Research Report On Menstrual Restriction And Perceived Stress Among Adolescent Girls Among School Going Adolescent Girls, Kailali, Nepal - Dahal, Alisha (H. : ĐHKT, 2020)
Fueled by ignorance and myth, menstrual restriction has had its root in Nepalese society since eras. With various Hindu mythologies, it is forced upon women so as they are unable to perform daily works as usual with such restrictions. The more severe form of restriction such as Chaupadi has killed many women and young child due to suffocation, snakebite, rape and other serious forms. Although it has been criminalized by the law no visible impact of the law has been seen yet. Excluding the hormonal imbalance and physical pain that women go through during such discriminatory practice, such hazardous practices also affect the mental health of the young girls which haven't been yet explored so for this reason this study is very important for the physical, social and psychological wellbeing of the adolescent girls and the community. The aim of this study is toaccess the prevalence and perceived stress due to menstrual restriction among Adolescent girls of Lower secondary school in Kailali District, Nepal.